UNRAVELING THE THREADS OF CONSTITUTIONAL INTERPRETATION: EXPLORING KEY PRINCIPLES (Journal of actual problems of jurisprudence, 2024)
The analysis looks at how each of these principles influences the process of constitutional interpretation and how they may conflict or complement each other. Such an analysis helps to better understand how the judicial system makes decisions based on these principles and how they affect legal proceedings and enforcement within the constitutional framework.The principles of constitutional interpretation encompass a nuanced framework that defines the understanding and application of a country's foundational legal document. The cornerstone is textualism, which emphasises a literal reading of the constitutional text in order to ascertain its original intent. Such an approach is often aligned with originalism, which asserts that the constitution should be interpreted in accordance with the understanding of its framers.Conversely, living constitutionalism recognises the ability of the document to adapt to changes in society over time. It asserts that the meaning of the constitution evolves to address contemporary issues while preserving its core values.Precedent plays a crucial role and judicial decisions serve as a guide for future interpretations. The doctrine of stare decisis promotes consistency and stability in the interpretation of the law, thus promoting predictability in the application of constitutional principles.The structural approach to interpretation involves analysing the constitutional framework and the distribution of powers among the branches of government. This approach recognises that the architecture of the constitution reflects a deliberate choice in favour of maintaining a system of checks and balances.Keywords: Constitution, interpretation, princeples, constitutional law, origanalism, textualism, living constitutionalism, judicial review, historical context, strict construction, precedent, broad construction, original meaning, contextual interpretation, evolving standarts, rule of law, stare decisis.